Digestion of Human Milk Oligosaccharides by Bifidobacterium breve in the Premature Infant. Issue 4 (October 2017) - Underwood, Mark A.; Davis, Jasmine C.C.; Kalanetra, Karen M.; Gehlot, Sanjay; Patole, Sanjay; Tancredi, Daniel J.; Mills, David A.; Lebrilla, Carlito B.; Simmer, Karen
ABSTRACT: Objective: The aim of this study was to measure consumption and absorption of human milk oligosaccharides (HMOs) in a cohort of premature infants treated with probiotic Bifidobacterium breve. Methods: Twenty-nine premature infants (median gestational age 28 weeks, range 23–32 weeks) cared for in the neonatal intensive care unit of the King Edward and Princess Margaret Hospital in Perth, Australia, were treated with B breve at a dose of 1.66 billion organisms per day. Samples of feces, urine, and milk were obtained at initiation of the probiotic and again 3 weeks later. 16S ribosomal RNA from the feces was analyzed by next-generation sequencing. Quantitation of HMO content of the milk, urine, and feces was performed using nano-high-performance liquid chromatography-chip/time-of-flight mass spectrometry. Results: There was heterogeneity in colonization with bifidobacteria. "Responders" received milk with higher percentages of fucosylated HMOs and had higher percentages of bifidobacteria and lower percentages of Enterobacteriaceae in their feces than "nonresponders." Several individual HMOs in the milk were associated with changes in fecal bifidobacteria over time. Changes over time in milk, fecal, and urine HMOs suggested heterogeneity among HMO structures in consumption by microbes in the gut lumen and absorption from the intestine. Conclusions: Colonization of the premature infant intestinal tract with probiotic B breve is influenced by prebiotic HMOs. B breve is a selective consumer of HMOs in the premature infant. Abstract : Supplemental Digital Content is available in the text